Clinical trials and the African person : a quest to re-conceptualize responsibility - Iyioke, Ike V. (Value Inquiry Book Series, 2018)
Clinical Trials and the African Person aims to position the African notion of the self/person within the clinical trials context. As opposed to autonomy-based principlism, this other-regarding/communalist perspective is the preferred alternative model. This tactic draws further attention to the inadequacy of the principlist approach particularly in multicultural settings. It also engenders a rethink, stimulates interest, and re-assesses the failed assumptions of universal ethical principles. As a novel attempt that runs against much of the prevailing (Euro-American) intellectual mood, this approach strives to introduce the African viewpoint by making explicit the import of the self in a re-contextualized arena, meaning within the community and a given milieu. Thus, research ethics must go beyond autonomy-based considerations for the individual, to rightly embed him/her within his/her community and the environment.